Inspirational of biomimicry approach through creating jewellery design - Hashim, Hema Zulaika; Abd Rahman, Khairul Aidil Azlin; Alli, Hassan; Raja Ahmad Effendi, Raja Ahmad Azmeer; Norzaman, Nor Ziratul Aqma (Malaysia Technical Scientist Association, 2019)
Creativity philosophy is the artistic result of a designer's self-expression in his/her freedom in the creation of a masterpiece which is strongly rooted to the soul of the designer. The issue is, have designers as well as jewellers indentified and learned to link improvement initiatives to minimize the gaps in key business activity and performance? This paper exproles how designers steamline design methods which will help to improve and maximize the workflow od jewellery designing. Design ideas and inspiration in this study aim to create signature influences with distincive aesthetics in jewellery designing. While the market is undergoing an unstable phase, many designers explore classic nature theme. The biomimicry approch is adopted in jewellery designing to demonstrate the ability of desicnomic consideration on economic views. Jewellery designers use a variety of techniques to study the nature theme criteria for design adaptation , to enhance the charecter of motif for better jewellery identety and to establish the philosophy of design elements in designing jellery. An investigative method should be taken to identify if creative philosophy defines quality in reaching agreed customer nesesties at low-cost product. In summery, the most infinite source of inspiration most expressive to consumer is dominant motifs such as flower in designing ideas.